Contribution to the study of Peruvian Wart - Foreword - Battistini, Telémaco S. (1925)
The purpose of this preliminary note is to present, in summary form, the results of our research on transmission of the virus in the Peruvian wart, in its malignant form (complete blood face), the inner monkeys.